Sistem Informasi Sekolah Di SurakartaBerbasis Website - Nugraha, Roni Sulistya, Nurgiyatna, S.T., M.Sc., Ph.D (2016)
Education is an important means to create a human resources able to be competitive in the nation's progress. Information can only be public schools earn through print media is still insufficient to reach widely. Over the development of communication technology and school information delivery can be served by using the website. The website is a collection of web pages, which is summarized in a domain or sub-domain, whose place is in the Word Wide Web (WWW). Given the importance of delivering information to the public school supported by the development of information technology continues to develop the necessary systems that can present school information accurately and easily understood society. This research aims to design and make the web-based system informsi school. The system is equipped with profile information schools, school facilities, school achievement and school documentation that can give an idea of the school. So parents can choose the school for their child in accordance talents and interests of the child. The system is designed to use PHP and MySQL database. Based on testing with a black box system, the system can be run in accordance with needs. In addition, the questionnaire results showed that 86.25% of respondents said that the system is made very helpful. Key Word : School, System Information, Technology, Website